Scheduling for VGOS Twin-Telescopes - Gnilsen, Paul (My University, 2016)
The technique of Very Long Baseline Interferometry (VLBI) allows the estimation of all five Earth Orientation Parameters (EOP), the International Celestial Reference Frame (ICRF) and it is a primary contributor to the International Terrestrial Reference Frame (ITRF), in particular with information about its scale. The International VLBI Service for Geodesy and Astrometry (IVS) aims at an improvement of accuracies for the next generation VLBI system by one order of magnitude, as compared to today’s level. This concerns the accuracies of the station positions and velocities that should be achieved at the 1 mm and 0.1 mm/year level, respectively, within the next years. Therefore a concept has been developed which was called VLBI2010 and then VLBI Global Observing System (VGOS). To reach these ambitious aims new VLBI Twin Telescopes (TT) are built next to already existing radio telescopes. The smaller TT, which are faster in their slewing movement, shall contribute to the goals of VGOS by an increasing number of scans and observations per site at a time. This study covers the utilisation of TT and goes into more detail about suchlike stations at the sites of Onsala in Sweden and Wettzell in Germany, which are in the works and are already built respectively. Therefore a global VLBI campaign named CONT11, which was held in September 2011, is rescheduled and simulated to compare the results between the subjoined TT and all other thirteen participating stations from this network of telescopes. As expected the distribution and absolute number of scans and observations in conjunction with these TT surpass the other antennas. Also the differences between simulated and estimated zenith delays are smaller for TT. However, baseline length repeatabilities derived from Monte Carlo simulations do not yield improved values for TT for the scheduling strategies tested in this thesis. Consequently more research for scheduling Twin Telescopes is required.
Keywords: Grundläggande vetenskaper; Geovetenskap och miljövetenskap; Basic Sciences; Earth and Related Environmental Sciences